Intoxication by mining revenues. San Marcos district politics after twelve years of Antamina’s presence - Salas Carreño, Guillermo (2010)
This paper describes and analyses the changes in local politicstaken place in the district of San Marcos (Huari, Ancash) associatedwith the arrival of the Canon Minero – a fraction of taxes paid byAntamina mining company to the Peruvian State. Canon Minero hasincreased sudden and spectacularly the municipality’s funds so muchthat currently San Marcos in «ones of the Peruvian richest districts».The paper pays attention to the municipal elections of 2006 and theimplementation of the Plan Piloto de Mantenimiento de la InfraestructuraPública, a program of temporary work for all San Marcos’citizens. The latter was key for launching a novel alliance betweenthe municipality and the rural population, particularly with the ConoSur composed by hamlets which were traditionally unimportantactors in district politics. Hence, district politics had stopped to bedominated by the struggle between two factions of former landlordfamilies and had become articulated by the opposition between therural hamlets and the town of San Marcos with the emergence ofethnic political claims. Also, local politics ceased to revolve aroundAntamina and has become entangled with struggles over the administrationof Canon Minero. Rural communities which have directnegotiations with Antamina remain important political actors whichare independent from the municipality and are even oppose to it.